VD_FINDINFO HC / 2010 / 578 vom 8. September 2010 - VD Tribunal cantonal (2010)
DROIT DU TRAVAIL, RÉPRIMANDE, SOMMATION, DROIT CANTONAL, FONCTIONNAIRE | 451 ch. 2 CPC, 452 al. 1ter CPC, 452 al. 2 CPC, 46 LJT, 16 al. 1 LPers-VD, 50 LPers-VD, 59 al. 3 LPers-VD